Tropical maize (Zea mays L.) - Edmeades, G.O.; Trevisan, W.; Boddupalli, P.M.; Campos, Hugo (Springer, 2017)
From its origins in Mexico, maize has spread throughout the cropping world and now has the largest annual production of any cereal crop. Maize adapted to the tropics has a shorter breeding history than its temperate equivalent, and maize yields in the tropics average 46% those of temperate regions. Diverse microclimates in its center of origin in Mexico resulted in a great diversity of landraces, and early improvement focused on identifying and compositing the most productive of these into genetically diverse populations that have subsequently formed the basis of modern inbred line extraction and pedigree breeding. The International Maize and Wheat Improvement Center (CIMMYT) has been the focus of much of this research for the past 50 years, and they, along with multinational seed companies, have been largely responsible for the major movements of elite tropical maize germplasm to Africa and Asia. Crop improvement has focused primarily on changing biomass partitioning by reducing plant height, increasing ear growth, reducing barrenness, and consistently focusing on increasing biotic and abiotic stress tolerances. Photoperiod sensitivity and tassel size, however, remain high and harvest index and tolerance to plant density low relative to temperate maize. Tropical maize breeding programs have shown genetic gains of around 100 kg/ha/year under optimal conditions, though less under abiotic stress. Genetic rates of gain have averaged 1–2% annually despite the high incidence of stresses in target environments, and today farm yields in tropical environments are increasing at the same rate (70–80 kg/ha/year) as in temperate production areas. Although open-pollinated varieties (OPVs) have been largely superseded by hybrids, there are niches in low-yielding environments or where commercial seed companies are dysfunctional where OPVs have a role. Tropical maize breeding programs should maintain their focus on yield stability in stressed environments, increased yield potential by further changes in plant morphology and partitioning, precise high-throughput phenotyping, and the systematic adoption of real-time marker-assisted selection (MAS). Considerable improvements in technologies that shorten the selection cycle have been made, e.g., the combination of doubled haploid inbred line production and MAS, especially genomic selection. Effective management of the deluge of genotypic and phenotypic data is a continuing priority. Impact will however only be achieved by increasing the rate of varietal turnover at the farm level so the challenges of global warming can be effectively met by the new generation of stress-tolerant maize cultivars. This can only come about through effective private-public partnerships in the seed sector and in a continued investment in well-trained motivated plant breeders and agronomists committed to quality fieldwork with the widest possible array of useful genetic variation.